2021
DOI: 10.3847/1538-4357/abf430
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Soft Excess in ESO 362-G18 Revealed by XMM-Newton and NuSTAR Spectroscopy

Abstract: We present a detailed spectral analysis of the joint XMM-Newton and NuSTAR observations of the active galactic nuclei (AGNs) in the Seyfert 1.5 Galaxy ESO 362-G18. The broadband (0.3-79 keV) spectrum shows the presence of a power-law continuum with a soft excess below 2 keV, iron Kα emission (∼6.4 keV), and a Compton hump (peaking at ∼20 keV). We find that the soft excess can be modeled by two different possible scenarios: a warm (kT e ∼ 0.2 keV) and optically thick (τ ∼ 34) Comptonizing corona, or with a rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 116 publications
5
27
0
1
Order By: Relevance
“…Jiang et al 2018;García et al 2019). If in reality there is indeed a warm corona, its presence would make it more difficult to constrain the soft X-ray shape of the reflection spectrum (Xu et al 2021). Since we believe our models to be most robust for E 3 keV, we ran an alternative fit ignoring E < 3 keV (Model 3), and found that the 3σ error on H 0 almost doubles (dH 0 ≈ 60 km s −1 Mpc −1 ) compared to the other fits.…”
Section: Soft X-raysmentioning
confidence: 99%
“…Jiang et al 2018;García et al 2019). If in reality there is indeed a warm corona, its presence would make it more difficult to constrain the soft X-ray shape of the reflection spectrum (Xu et al 2021). Since we believe our models to be most robust for E 3 keV, we ran an alternative fit ignoring E < 3 keV (Model 3), and found that the 3σ error on H 0 almost doubles (dH 0 ≈ 60 km s −1 Mpc −1 ) compared to the other fits.…”
Section: Soft X-raysmentioning
confidence: 99%
“…Jiang et al 2018;García et al 2019). If in reality there is indeed a warm corona, its presence would make it more difficult to constrain the soft X-ray shape of the reflection spectrum (Xu et al 2021). Since we believe our models to be most robust for 𝐸 3 keV, we ran an alternative fit ignoring 𝐸 < 3 keV (Model 3), and found that the 3𝜎 error on 𝐻 0 almost doubles (𝑑𝐻 0 ≈ 60 km s −1 Mpc −1 ) compared to the other fits.…”
Section: Soft X-raysmentioning
confidence: 99%
“…The properties of the inner accretion discs of AGNs are measured through X-ray reflection spectra, which show a soft X-ray excess below ∼ 2 keV, a broad emission profile due to Fe K lines at ∼ 6.4 − 7.1 keV, and Compton hump above 10 keV (e.g. Marinucci et al 2014;Matt et al 2014;Zoghbi et al 2015;García et al 2019;Xu et al 2021). The physical modeling of these features provides direct probes for the inner disc atmosphere and black hole spin (e.g.…”
Section: Introductionmentioning
confidence: 99%